2022
DOI: 10.3390/medicina58081112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Pediatric Emergency Medicine: A Systematic Review

Abstract: (1) Background and Objectives: The COVID-19 pandemic has considerably affected clinical systems, especially the emergency department (ED). A decreased number of pediatric patients and changes in disease patterns at the ED have been noted in recent research. This study investigates the real effect of the pandemic on the pediatric ED comprehensively by performing a systematic review of relevant published articles. (2) Materials and Methods: A systematic review was conducted based on a predesigned protocol. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…A US study even found that visits had not yet normalized until January 2022 [ 23 ]. The reasons for this may include parents’ fear of contracting COVID-19 in EDs [ 36 38 ], fewer infections due to containment measures such as wearing face masks at public gatherings [ 38 ], and longer lasting and more drastic COVID-19 measures due to a more severe course of the pandemic in the two neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A US study even found that visits had not yet normalized until January 2022 [ 23 ]. The reasons for this may include parents’ fear of contracting COVID-19 in EDs [ 36 38 ], fewer infections due to containment measures such as wearing face masks at public gatherings [ 38 ], and longer lasting and more drastic COVID-19 measures due to a more severe course of the pandemic in the two neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…The most common diagnoses in pediatric EDs are breathing difficulties, febrile illnesses, and gastroenterits [ 39 ], which mostly affect young children [ 40 ]. These diseases declined during and after the nationwide installation of NPIs [ 38 , 41 ]. The lower rates of communicable diseases in this age group were probably caused by fewer contacts with other children and less parent- or siblings-to-child-transmission because of hygiene and containment measures.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this may include parents' fear of contracting COVID-19 in EDs (18, 19,33), fewer infections due to containment measures such as wearing face masks at public gatherings (33), and longer lasting and more drastic COVID-19 measures due to a more severe course of the pandemic in the two neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PED volumes declined sharply, leading to reduced pediatric emergency physician hours in many PEDs. 23 Additionally, at some institutions, pediatric-trained staff (physicians, nurses, respiratory therapists, etc) were given temporary change in delineation of privileges to expand scope of practice and were redeployed to care for adults as part of the disaster response, or were transitioned to providing telehealth services. 15,16,24 Non-emergency medicine trainees (medical students, residents, and fellows) who were originally assigned to work within the PED experienced restrictions on patient care provision and procedures, were reassigned to care for adults, or away from the ED altogether.…”
Section: Ed Staffing and Scope Of Practicementioning
confidence: 99%
“…The number of critically ill patients in many hospitals exceeded the number of critical care and ED beds, prompting the need for other inpatient areas to serve as intensive care units. At the same time, PED volumes declined sharply, leading to reduced pediatric emergency physician hours in many PEDs 23 . Additionally, at some institutions, pediatric‐trained staff (physicians, nurses, respiratory therapists, etc) were given temporary change in delineation of privileges to expand scope of practice and were redeployed to care for adults as part of the disaster response, or were transitioned to providing telehealth services 15,16,24 .…”
Section: Ed and Healthcare System Operationsmentioning
confidence: 99%